Puericultura e diagnóstico precoce do transtorno do espectro autista na atenção primária à saúde: avaliação da implantação de instrumento de triagem - Souza, Ana Élida Nogueira (2024)
Childcare is a set of activities that provides, among other things, the great opportunity to identify disorders in the child's growth and development in the Primary Health Care setting. In view of the improvement of actions, associated with the exponential increase in the number of cases of children with Autism Spectrum Disorder (ASD) in Brazil, the Ministry of Health recommends the use of the validated screening instrument M-CHAT, a scale composed of 20 questions which when applied add up points indicating the need for in-depth analysis of the child's neuropsychomotor development, due to suspicion of ASD. This tool can be used by any healthcare team professional. Therefore, knowing the concept and action of M-Chat in primary care becomes fundamental. In this study, our main objective was to analyze the applicability of this screening instrument for ASD during childcare consultations in primary care. To this end, action research was developed with doctors and nurses, a total of 14 professionals, from two Family Health Centers (CSF) that had the highest number of cases of people with ASD geoprocessed by the Primary Care Coordination in Sobral, Ceará. They were representatives of the municipal headquarters. The research took place during the year 2023. Four stages were carried out. In the first, a questionnaire was applied to identify the participants' prior knowledge and, in the second, planning was carried out based on the data collected. In the third stage, a workshop was developed, where basic concepts, historical aspects, epidemiology, etiology, signs and symptoms, diagnosis, treatment and line of care for people with ASD in the city of Sobral-CE. Dynamics were carried out simulating real situations in the context of applying the screening instrument for ASD, the M-CHAT, in order to share information with professionals, as well as recommend references on the topic, reinforcing the importance of being carried out in childcare. In the fourth stage, the previous intervention was evaluated through a new questionnaire after the action phase to qualify and examine research and the applied method. As a result, it was observed that the use of M-CHAT is not a reality within the CSFs in the city of Sobral - CE, in addition to not being known by most professionals who work in primary health care. Of the participants, more than 70% had less than 5 years in Primary Care. Just over 50% reported participating in continuing education. 78.6% stated that they are repeatedly asked by their parents about ASD. However, the majority said they were insecure about the topic. After the action, when asked whether they considered themselves prepared to apply M-CHAT in childcare, 100% responded yes. These results were presented to the health teams and, in this way, proposals, reflections and health actions were made in light of what was discussed, improving health practices egarding the early diagnosis of ASD in primary care child care.